MAGNETIC FIELDS OF ISOLATED NEUTRON STARS: EVIDENCE FOR DECAY - Popov, S. B.; Prokhorov, M. E. (Одеські астрономічні публікації, 2017)
We show, that different types of isolated neutron stars (INSs) show evidence in favor of magnetic field decay in these objects and discuss how observations of INSs can help to constrain models of field decay.